2013
DOI: 10.1111/eth.12062
|View full text |Cite
|
Sign up to set email alerts
|

Sequential Polygyny During Egg Attendance is Rare in a Tree Frog and Does not Increase Male Fitness

Abstract: Sequential polygyny is a reproductive strategy that allows males to continue to mate and compensates for the loss of future breeding opportunities incurred by parental care (i.e. egg attendance). Using the frog Kurixalus eiffengeri, we tested predictions that (1) attending males fathered two, overlapping clutches; and (2) that double clutching leads to improved offspring numbers. Using five microsatellite DNA markers, we genotyped 15 pairs of overlapping clutches, which differed slightly in developmental stage… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
(109 reference statements)
0
5
0
Order By: Relevance
“…To further complicate matters, even in cases where adults can care for multiple clutches, it is not necessarily correlated with increase in adult fitness (Cheng et al. ), on top of which individuals could be providing care to unrelated embryos (Chen et al. ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…To further complicate matters, even in cases where adults can care for multiple clutches, it is not necessarily correlated with increase in adult fitness (Cheng et al. ), on top of which individuals could be providing care to unrelated embryos (Chen et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…Of course, costs of egg attendance can vary greatly for either parent, both between and within species, depending on time and energy invested. To further complicate matters, even in cases where adults can care for multiple clutches, it is not necessarily correlated with increase in adult fitness (Cheng et al 2013), on top of which individuals could be providing care to unrelated embryos (Chen et al 2011). It is clear, however, in the case of C. hansenae that benefits of egg attendance exceed costs, as clutches are unable to develop without attending females.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies have demonstrated other complex ways that parental care can benefit offspring: larger size of brooding males in A. obstetricans and Alytes cisternasii (Raxworthy 1990;Márquez 1993), sequential vs. nonsequential clutch attendance in K. eiffingeri (Cheng et al 2012), and differences expressed among allopatric color morphs in O. pumilio (Dugas and Richards-Zawacki 2015). Such findings suggest that we are only beginning to understand the complex interactions between parental care and offspring fitness in anurans.…”
Section: Anuransmentioning
confidence: 94%
“…To date, genetic analyses of mating systems have been made for <20 species, representing <1% of all described species. Nevertheless, considerable diversity has already been uncovered, with reports of mating systems ranging from extreme monogamy and polygyny, to extreme polyandry and polygynandry (Brown, Morales, & Summers, 2010;Byrne & Keogh, 2009;Cheng, Chen, Yu, Roberts, & Kam, 2013;Knopp & Meril€ a, 2009;Laurila & Sepp€ a, 1998;Lod e & Lesbarr eres, 2004;Ringler, Ringler, Jehle, & H€ odl, 2012;Wang, Xie, Wang, & Jiang, 2014). Critically, however, the vast majority of these studies have only considered a fraction of a species' breeding season or sampled a very small subset of breeding individuals and offspring.…”
mentioning
confidence: 99%